Morphology evolution in biaxially stretched polyethylene terephthalate and prediction of final elastic properties - Thanh Tung Nguyen; Yun-Mei Luo; Luc Chevalier (Polymer Testing, 2025)
Polyethylene terephthalate (PET) crystallization and macromolecular orientation during biaxial stretching near Tg was investigated using in-situ synchrotron Small-angle X-ray scattering (SAXS). Morphological evolution is tracked under constant-width (CW) and equal-biaxial (EB) loading.From the final microstructure, we estimate the elastic properties of stretched PET using the two-step analytical homogenization already used, successfully, on blown bottle. Furthermore, a parametric uncertainty analysis on the elastic properties of the oriented amorphous phase is performed to assess the sensitivity of the elastic moduli using known cases from bottle studies as reference. Monte Carlo simulations validated the model's reliability by confirming the convergence of results in terms of both mean values of modulus and its logarithm. Finally, these predictions are validated through experimental measurements of the mechanical properties of the CW and EB on micro-specimens cut out from the biaxially stretched cross specimen and an empirical law is proposed to fit the rigidity of oriented amorphous phase.